2013
DOI: 10.1016/j.jvs.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Compression stockings significantly improve hemodynamic performance in post-thrombotic syndrome irrespective of class or length

Abstract: Compression significantly improved all hemodynamic parameters on air plethysmography. However, the hemodynamic benefit did not significantly change with the class or length of stocking. These results support the liberal selection of a GEC stocking based on patient preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
2
48
0
2
Order By: Relevance
“…The performance of a stocking at reducing calf volume and reflux has been investigated recently in patients with post-thrombotic syndrome. 23 That study reported significant reductions in the venous volume and the venous filling index. Once a global index of stocking performance can be measured, then it may provide a way of selecting stockings based on their overall haemodynamic characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…The performance of a stocking at reducing calf volume and reflux has been investigated recently in patients with post-thrombotic syndrome. 23 That study reported significant reductions in the venous volume and the venous filling index. Once a global index of stocking performance can be measured, then it may provide a way of selecting stockings based on their overall haemodynamic characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…14 The reduction in diameter may be explained in general terms through a reduction in flow and a diminished venous reservoir. Stockings have been shown to reduce the venous volume in the calf with air-plethysmography, 24 and excision of varicose tributaries has been shown to have beneficial effects on the GSV. 25 It is a common observation that varicose veins do not fully collapse when the leg is elevated.…”
Section: Discussionmentioning
confidence: 99%
“…92 Compression stockings could also decrease the incidence of venous thromboembolism following VVs surgery, and improve hemodynamic performance in post-thrombotic syndrome. 93 Pharmacological treatment of VVs includes venotonic drugs that improve venous tone and capillary permeability, and reduce leukocyte infiltration. Venotonic drugs include naturally occurring plant extracts and glycosides such as α-benzopyrones (coumarins), γ-benzopyrones (flavonoids), plant extracts (blueberry and grape seed, ergots, Ginkgo biloba), and saponosides (Centella asiatica, escin, horse chestnut seed extract, ruscus extract).…”
Section: Management Of Vvsmentioning
confidence: 99%